NILAI ADAPTIF-REFLEKTIF DALAM SINDIR-KIAS SEBAGAI WUJUD DINAMIKA KEBUDAYAAN BAHASA MINANGKABAU - Andri Azis Putra (Jurnal Filsafat "WISDOM", 2017)
Language is a vital issue in a culture. Minangkabau as a devoted clan to their oral tradition has a unique linguistic dynamics. Through the "proverbs" inherited from its predecessor, satire and metaphor take its place as the center of Minangkabau culture models. However, the misunderstandings of the Minangkabau people during this time of sindir-kias meaning is no longer makes the same morality standards. Therefore, this study aimed to find a conception which can restore the  "sindir-kias" in the life of the Minangkabau people in particular and the Indonesian people in general. This study is a research library by the hermeneutic method with the elements of methods, such as descriptions, verstehen, induction-deduction, inclusive language, and interpretation. The material object of this research is "sindir-kias" as the center of Minangkabau culture models. The formal object of this research is axiology with the assistance of analytic philosophy. This research found that in the culture of Minangkabau language, there are adaptive and reflective capabilities in developing satire (sindiran) and allegory (kiasan). This proves that the traditional Minangkabau is very open in its linguistic development, but also at the same time is able to reflect and internalize it to be the product of Minangkabau culture. The intersubjectivity value, in this case, takes a very important role. Therefore, the value of which is owned by language Minangkabau tradition is a value of "adaptive-reflective", thus ensuring the emergence of linguistic dynamics, which of course steer the model of Minangkabau culture.